A Corpus-Assisted Qualitative Analysis of Slang Expressions in Dreamworks’ The Boss Baby: Family Business - Yulianto, Andrias; Dira, Benito (International Journal of English and Applied Linguistics (IJEAL), 2025)
One of the varieties in language is slang, an informal style of language, characterized by constantly shifting vocabulary and its impact in strengthening group unity and social identity. This research investigated slang in an animated film by DreamWorks, The Boss Baby: Family Business using a qualitative approach. Through a qualitative research design, the researchers applied a corpus-assisted method. Data were gathered by repeatedly watching the film, extracting slang expressions from the dialogues, and validating meanings through slang dictionaries. The findings suggested a total of 40 slang words exist in the film, revealing six distinct aspects: clipping, compounding, acronyms, blends, metaphor, and affixation. This research also examined four particular types of slang: society slang, slang in publicity, slang in school and university, and medical slang. The most prevalent categories were publicity slang (13 items) and society slang (18 items). According to the findings, the most common types are clipping and compounding, which are employed to enunciate social belonging, lightheartedness, and closeness. Characters' slang choices diversified systematically, enabling the creation of their identities, allowing exchanges, and storylines. The study arrives at the conclusion that slang is a planned, multipurpose language strategy utilized in the movie that boosts audience engagement and character growth. Yet, this research was limited to a single cinematic element and prioritized primarily on character utterances within a particular context. On the grounds of that, future scholars are encouraged to broaden the scope by delving into comparative explorations throughout different movie genres or examining the development of slang in long-form media such as television series. Keywords: Characteristics of Slang Language, Slang language, Sociolinguistics, The Boss Baby: Family Business, Types of Language